2022
DOI: 10.1186/s13071-022-05292-w
|View full text |Cite
|
Sign up to set email alerts
|

Experiment in semi-natural conditions did not confirm the influence of malaria infection on bird attractiveness to mosquitoes

Abstract: Background Changes in host phenotype following parasite infection are often considered as host manipulation when they seem advantageous for the parasite. However, putative cases of host manipulation by parasites are rarely tested in field-realistic conditions. Infection-induced phenotypic change cannot be conclusively considered as host manipulation if no evidence shows that this trait is adaptive for the parasite in the wild. Plasmodium sp., the parasites causing malaria in vertebrates, are hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Additionally, a study by Lacroix et al [ 22 ] in the human malaria system found similar results. However, other studies have found that there was no evidence of this alteration, and perhaps a parasite avoidance by these mosquitoes [ 31 , 50 ]. These data support a modulation in flight activity by P. relictum in less overall flight activity and increased flight activity at peak host-seeking times, which could lead to an increase the transmission of this P. relictum parasite.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, a study by Lacroix et al [ 22 ] in the human malaria system found similar results. However, other studies have found that there was no evidence of this alteration, and perhaps a parasite avoidance by these mosquitoes [ 31 , 50 ]. These data support a modulation in flight activity by P. relictum in less overall flight activity and increased flight activity at peak host-seeking times, which could lead to an increase the transmission of this P. relictum parasite.…”
Section: Discussionmentioning
confidence: 91%
“…The effect of Plasmodium parasites on the behaviour of mosquito hosts has been explored in several studies with conflicting results [ 19 , 30 , 31 ]. Koella et al [ 21 ] demonstrated alterations to Anopheles gambiae mosquito biting behaviour that would improve the transmission of Plasmodium falciparum parasites, including an increase in multiple biting events.…”
Section: Introductionmentioning
confidence: 99%
“…This parasite avoidance behaviour has been demonstrated in fewer studies (see Lalubin et al ., 2012 ) when compared to a larger body of studies showing higher vector attraction to infected hosts (Cozzarolo et al ., 2020 ; Santiago-Alarcon and Ferreira, 2020 ). Nonetheless, some earlier studies also suggest the absence of any effect of infection status on vector attraction (Cozzarolo et al ., 2022 ).…”
Section: Evolutionary Consequences Of Vector Transmission For Vectorsmentioning
confidence: 99%